IMPLEMENTASI PENDIDIKAN EMANSIPATORIS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA DI PKBM BINA BANGSA DALAM MENJAWAB TANTANGAN MASA DEPAN PENDIDIKAN - Munandar, A. Hafid; Hidayah, Deni; Heerlina, Nina; Rosmuliawati, Ade Siti; Suwandari, Lilis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of emancipatory education to improve students’ learning independence at PKBM Bina Bangsa and its relevance in addressing the challenges of future education. Using a qualitative case study approach, the research was conducted at PKBM Bina Bangsa, Purwakarta, involving students, tutors, and administrators as participants. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed descriptively using the interactive model of Miles and Huberman. The findings show that emancipatory education was implemented through flexible curriculum planning, participatory organization, dialogical and reflective teaching methods, and feedback-based evaluation. This approach successfully empowered students to become more independent in managing their learning, more confident, and more critical in addressing problems. Despite limitations in facilities and tutor competencies, emancipatory education at PKBM Bina Bangsa has created an inclusive and transformative learning ecosystem that aligns with the national education policy of lifelong learning and 21st-century skills. Therefore, emancipatory education can be an effective strategy to improve the quality of nonformal education in Indonesia. Keywords: emancipatory education, learning independence, PKBM, nonformal education, lifelong learning;